FACTORS THAT INFLUENCE CONSUMERS' PERCEPTIONS OF THE FRONT OF PACK NUTRI SCORE LABEL ON PACKAGED COFFEE POWDER - Liasna Demkrina; Iskandarini; Sri Fajar Ayu (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to analyze public perceptions of the Front Of Pack Label Nutriscore on Packaged Ground Coffee and analyze the factors that can influence these perceptions. The research method used in this study is a descriptive quantitative method. The sample in this study was 100 respondents who were consumers of packaged coffee in Medan City. The data collection method used a questionnaire with a Likert scale. Data analysis in this study used multiple linear regression analysis using the SPSS version 25 program. Hypothesis testing in this study used a partial t test, simultaneous f test and determination coefficient test. The results showed that the partial T test showed that the t count value was 5.595 <t table 1.661 and had a significant value of 0.000> 0.05, so that partially internal factors had a significant positive effect on the Front Of Pack Nutri-Score Perception of consumers of packaged ground coffee in Medan City. The results of the partial T test show that the t-value is 2.738 < t-table 1.661 and the significance value is 0.007 < 0.05, so that partially external factors have a significant positive effect on the Front Of Pack Nutri-Score Perception of packaged ground coffee consumers in Medan City. Simultaneously, it produces a significant value of 0.000 < 0.05. So, simultaneously the independent variables have a significant positive effect on the Front Of Pack Nutri-Score Perception of packaged ground coffee consumers in Medan City. The results of the determination coefficient test show a value of 0.339. So it can be concluded that internal factors (X1) and external factors (X2) have an effect on the Front Of Pack Nutri-Score Perception of the community in Medan City by 33.9%. While the remaining 66.1% is influenced by variables outside the predicative of this study.